Ileocecal Adenocarcinoma and Ureteral Transitional Cell Carcinoma with Multiple Sebaceous Tumors and Keratoacanthomas in a Case of Muir-Torre Syndrome - Michael C. Lynch; Bryan E. Anderson (Dermatology Research and Practice)
Cutaneous neoplasms including sebaceous tumors, keratoacanthomas, and basal cell carcinomas with sebaceous differentiation can be markers of internal malignancy associated with the Muir-Torre Syndrome (MTS). We report a 56-year-old man with a diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) and ureteral transitional cell carcinoma who subsequently developed two sebaceous gland neoplasms and several keratoacanthomas, leading to the diagnosis of MTS. Our case highlights the clinical advantages of immunohistochemistry (IHC) in identifying mutations in the mismatch repair (MMR) genes responsible for both HNPCC and MTS. The importance of continued clinical suspicion in the dermatological assessment of patients with sebaceous neoplasms is emphasized.